Religion, language, race and ethnic voting. (October 2019) - Houle, Christian
Abstract: Why do some ethnic groups vote along ethnic lines while others do not? This article looks at whether the objective characteristics of ethnicity – in terms of language, religion and race – affect ethnic voting. I address three sets of questions: (1) are ethnic groups that are objectively different from other groups of their country more likely to vote ethnically? (2) is ethnic voting higher among groups that are linguistically, religiously and racially homogeneous? (3) do some ethnic markers, such as language, induce more ethnic voting than others? Using a dataset covering 142 ethnic groups and 49 democracies worldwide, I find that within-group similarity increases ethnic voting. On balance, however, there is little evidence that between-group difference or the identity of the ethnic dimension affect ethnic voting. These results suggest that a group's internal characteristics and the cohesiveness of its members play a key role in explaining its voting behavior.